Waterborne zinc bioaccumulation influences glucose metabolism in orange-spotted grouper embryos. (15th August 2021) - Zeng, Huiling; Zhang, Peifeng; Ye, Hengzhen; Ji, Yuxiang; Hogstrand, Christer; Green, Iain; Xiao, Juan; Fu, Qiongyao; Guo, Zhiqiang
Abstract: Fish embryos, as an endogenous system, strictly regulate an energy metabolism that is particularly sensitive to environmental pressure. This study used orange-spotted grouper embryos and stable isotope 67 Zn to test the hypothesis that waterborne Zn exposure had a significant effect on energy metabolism in embryos. The fish embryos were exposed to a gradient level of waterborne 67 Zn, and then sampled to quantify 67 Zn bioaccumulation and mRNA expressions of key genes involved glucose metabolism. The results indicated that the bioaccumulated 67 Zn generally increased with increasing waterborne 67 Zn concentrations, while it tended to be saturated at waterborne 67 Zn > 0.7 mg L −1 . As we hypothesized, the expression of PK and PFK gene involved glycolysis pathway was significantly up-regulated under waterborne 67 Zn exposure >4 mg L −1 . Waterborne 67 Zn exposure >2 mg L −1 significantly suppressed PCK and G6PC gene expression involved gluconeogenesis pathway, and also inhibited the AKT2, GSK-3beta and GLUT4 genes involved Akt signaling pathway. Our findings first characterized developmental stage-dependent Zn uptake and genotoxicity in fish embryos. We suggest fish embryos, as a small-scale modeling biosystem, have a large potential and wide applicability for determining cytotoxicity/genotoxicity of waterborne metal in aquatic ecosystem. Graphical abstract: Image 1 Highlights: The 67 Zn uptake in fish embryos increased with increasing waterborne 67 Zn levels. Glycolysis associated proteins were up-regulated under high 67 Zn exposure. Gluconeogenesis and Akt signaling pathways were suppressed by high 67 Zn exposure. Fish embryos are an ideal model for determining cytotoxicity/genotoxicity of waterborne metals. Abstract : Waterborne zinc bioaccumulation influenced glycolysis, gluconeogenesis and Akt signaling pathway in the fish embryos.